(3QSGdI GdLejgQjIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdHGQ GdYdGe hTcQJ YHOg GdgGOi GdEeGe ef GdYHO HgGA GdOjf hdSGf GdeDefjf hSfO GdehMOjf Edi GdCeQGA GdSGOI Bd JfhN s
(3BNQgG (B:s
(3hCf jai Hge hHLeGYI GdehMOjf Edi GdCaVd GdCTQa GdCYdi Efg Ydi Pdc bOjQ hGdMeO dehdGfG hMOg hdg GdTcQ Ydi efJg Ydi ChdjGFg HGdEeGe GdgGOi YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B50s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds